Cold sterilization of coconut water by membrane technology and UV-C - Aliwarga, Lienda; Joenputri, Fiena; Chandra, Livia; Julian, Helen (Jurnal Rekayasa Proses, 2023)
Coconut water contains amino acids, vitamins, antioxidants, and mineral, which are beneficial for human health. However, rapid degradation of coconut water due to the presence of protein, fat, and microbes has led to short shelf life and coconut water’s rancidity. Sterilization of coconut water by heat treatment has been proven to be effective in microorganism elimination, but results in major changes of coconut water’s sensory attributes. In this research, cold sterilization of coconut water was conducted by using ultrafiltration membrane and UV-C to preserve the sensory properties and nutritional components in coconut water. The radiation dose of UV-C and operating pressure of ultrafiltration membrane was varied to obtain the optimum operating condition. The sterilization process by UV-C did not remove fat and protein, which are the rancidity-causing components. In ultrafiltration sterilization, fat and protein can be removed by 74% and 31.37%. Superior microorganism elimination by ultrafiltration was obtained at 99.9999%, compared to that by UV-C at 90%. The ultrafiltration also retained the coconut water’s pH, total soluble solid, and flavor, while improved its clarity. At optimum operating pressure of 0.25 bar, the coconut water’s shelf life of 3 days, according to the Standar Nasional Indonesia (SNI), can be achieved.